Guidelines to measurements of reproducible contact angles using a sessile-drop technique. Issue 4 (1st December 2013) - Drelich, Jaroslaw
Abstract : The current broad interest in wetting characterization of solid surfaces is driven by recent advances in the formulation of surfaces and coatings that are superhydrophobic, superhydrophilic, oleophobic, oleophilic and so on. Unfortunately, the contact angle data presented in many publications raise some concerns among the surface chemists and physicists who work with contact angle measurement techniques on a regular basis. In those articles, best practices are often ignored, and the data presented are limited to the static contact angles measured for small droplets, a few times smaller than typically recommended. The reported contact angles are neither advancing nor receding, and their reproducibility in different laboratories is therefore questionable. In this note, guidelines to measurements of reproducible and reliable advancing and receding contact angles are summarized.